Postos comunitários: uma alternativa para o sistema de saúde Community health centers: an alternative for the health system - João Claudio Lara Fernandes; João Guerra de Castro Monteiro (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1997)
Considerando a atual conjuntura de reorganização das relações entre o Estado e a sociedade civil, os autores propõem, para a área da saúde, uma alternativa intermediária entre as propostas estatizantes e privatizantes, que consiste na organização de postos de saúde geridos por entidades locais e conveniados ao Sistema Único de Saúde. Para sustentar esta proposição, é apresentada a experiência desenvolvida há 12 anos na favela da Rocinha, onde uma associação de moradores construiu e administra um serviço de saúde. É destacada a eficiência do trabalho, o que é atribuído a um maior controle social sobre o serviço, bem como às suas características geográficas, que favorecem a utilização de abordagens terapêuticas diversificadas. São apresentadas propostas que visam a dar uma maior sustentação a esta alternativa, como a elaboração de convênios diretos com associações de moradores, atualmente impedidos pela regulamentação do Ministério da Saúde, e a ampliação a estes postos de alguns critérios de remuneração, ora restritos a instituições governamentais. Reflecting on the current reorganization of the relationship between the state and civil society, the health care field is involved in an intense debate over the organization and use of government and private health services. The authors propose an alternative, consisting of the implementation of primary health care clinics, managed by local institutions and funded by the Unified Health System. To support this proposition, they report on the current experience at the Rocinha slum in Rio de Janeiro, where a community health center was built by the neighborhood association 12 years ago and has been managed by the community since then. The hospital referral rate at the clinic, requests for laboratory tests, and use of precriptions have been considerably limited, although these services are available. These low rates are attributed to the possibility of closer social control by the community, as well as to the geographical features of the center, favoring a broader perception of both health problems and treatment. In order to provide more substantial support to the proposed centers, some suggestions are presented, like the implementation of direct agreements between the government and neighborhood associations (not allowed under current legislation) and expanding potential sources of funding for the health centers, currently restricted to government programs.